Convergence effect of droplet coalescence under AC and pulsed DC electric fields. (October 2021) - Huang, Xin; He, Limin; Luo, Xiaoming; Xu, Ke; Lü, Yuling; Yang, Donghai
Highlights: The convergence effect in the AC and pulsed DC electric fields is discovered. The equivalent response mechanism of droplets are revealed. The critical f above which the shortest distance curve does not change is obtained. Abstracts: The coalescence behaviors of two neutral droplets suspended in silicone oil under the alternating current (AC) and pulsed direct current (DC) electric fields are investigated by experiments and numerical simulations. The distribution evolutions of electric force and velocity field during the droplet coalescence under the AC and pulsed DC electric fields are analyzed. The relationship between electric field excitation and droplet interface response is illustrated. The equivalent response mechanism of droplets under the high-frequency AC and pulsed DC electric fields and under the DC electric fields is revealed. The relationship of droplet dynamic behaviors under the DC electric field and under the AC and pulsed DC electric fields are established. The critical electric field frequencies above which the shortest distance curves no longer change under the AC and pulsed DC electric fields are obtained. These new findings are significant for the optimization of electrostatic coalescence. Graphical abstract: Image, graphical abstract